PENGEMBANGAN BUKU CERITA DIGITAL BERBASIS NILAI EMPATI UNTUK MENINGKATKAN LITERASI MEMBACA SISWA SEKOLAH DASAR - Solihudin, Muhamad; Yulina Ismiyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low reading literacy skills and weak empathy of elementary school students remain issues that require attention, despite the implementation of various literacy and character strengthening policies. This study aims to develop a digital storybook based on empathy values ​​to improve elementary school students' reading literacy and to describe its feasibility, practicality, and effectiveness as a learning medium. The study used a research and development method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The subjects were 30 fourth-grade students of Begeg Public Elementary School, Sukabumi City, and the class teacher as the media user. Data were collected through validation sheets from material experts, media experts, and language experts; reading literacy tests; and teacher and student response questionnaires. The validation results showed that the digital storybook was in the very feasible category with an average score of 90% for material experts, 87.5% for media experts, and 88.75% for language experts. Teacher and student responses indicated a very practical category with an average score of 3.70 for teachers and 3.50 for students on a 4-point Likert scale. The results of the effectiveness test showed an increase in the average reading literacy score from 62.00 (pretest) to 82.00 (posttest) in 30 students, with an average N-gain value of 0.53 (moderate category), as well as a significant difference based on the t-test. Thus, the digital storybook based on empathy values ​​is declared feasible, practical, and effective to be used as a learning medium to improve reading literacy while instilling empathy values ​​in elementary school students.